Factors associated with frailty progression in community-dwelling older adults: A cross-sectional observational study - Yuko Sawada; Akihiro Kakuda; Emiko Tanaka; Etsuko Tomisaki; Taeko Watanabe; Munenori Matsumoto; Rika Okumura; Hiroshi Kinoshita; Tokie Anme (Archives of Gerontology and Geriatrics Plus)
This cross-sectional observational study aimed to identify factors associated with frailty status in community-dwelling older adults. A total of 188 older adults (mean age: 75.9 ± 6.7 years) attending municipal exercise facilities between 2019 and 2022 were included. Data were collected on participants' basic characteristics, physical fitness, and scores from the Kihon Checklist (KCL). Frailty status was classified into robust (KCL score ≤3), pre-frail (4–7), and frail (≥8) groups based on established criteria. Group differences were analyzed using the Kruskal–Wallis test with Bonferroni correction for multiple comparisons. Significant differences among the robust, pre-frail, and frail groups were observed in most physical fitness and frailty-related items, particularly grip strength, walking ability, and lifestyle-related functions, except for cognition and depression. These findings indicate that specific domains of physical function are significantly associated with frailty status. Interventions targeting a broad range of physical fitness factors are essential to mitigate frailty in older adults.